If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + 5) = 7(x + -3) Reorder the terms: 5(5 + x) = 7(x + -3) (5 * 5 + x * 5) = 7(x + -3) (25 + 5x) = 7(x + -3) Reorder the terms: 25 + 5x = 7(-3 + x) 25 + 5x = (-3 * 7 + x * 7) 25 + 5x = (-21 + 7x) Solving 25 + 5x = -21 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 25 + 5x + -7x = -21 + 7x + -7x Combine like terms: 5x + -7x = -2x 25 + -2x = -21 + 7x + -7x Combine like terms: 7x + -7x = 0 25 + -2x = -21 + 0 25 + -2x = -21 Add '-25' to each side of the equation. 25 + -25 + -2x = -21 + -25 Combine like terms: 25 + -25 = 0 0 + -2x = -21 + -25 -2x = -21 + -25 Combine like terms: -21 + -25 = -46 -2x = -46 Divide each side by '-2'. x = 23 Simplifying x = 23
| 8x-5+2=14 | | 2x-2=3x+2+7 | | -144=6(4m+5)-6 | | 1+6(-8r+7)=-101 | | x+20=7x+8 | | 5-4x+6x=17 | | 7(3x-1)= | | A=267 | | 9=-5b-4b | | 7(2x+1)= | | 2k=26 | | -13=-8+v/3 | | x^2-4x-12=20 | | m/11=-14/11 | | 7=r/10 | | 11-43=5(x-1)-7 | | 2x+x+3=12 | | 2x-20=x+12 | | n/11=-12 | | (7x-10)(2x+3)= | | -6=a/18 | | Y=-7E-05X+2.7761 | | (3x-9)(2x+7)= | | 11x+9=5+27 | | 20-3x=2x+4 | | 40+40(0)+1= | | 3-7n+2=12 | | -45=6x-9 | | -75=-5a-5 | | 3x=5-(-19) | | 6.3=0.7 | | 6=w/9.6 |